An exploratory study of school librarians' emotional response to change in the workplace - Houston, Cynthia (2021)
Background. The library field is changing constantly as a result of changes in information access and technology innovations. Librarians are part and parcel of the change process, either as the initiators or primary recipient of change. Objectives. The goals of this study were to understand librarians’ emotional responses during the change process and the types of changes they were experiencing. School librarians in the United States were the subjects of this study. Methods. The study used exploratory survey methodology to gain a preliminary understanding of the types of changes school librarians were experiencing and how they were responding to these changes. Results. Overall, school librarians reported that they experienced negative emotions as a response to change, particularly discouragement. The results of this study indicated that school librarians responded negatively to change when it was imposed externally. School librarians were more positive about change when they had some level of influence over the changes being made. Novice librarians were most positive about change. In all cases, school librarians felt slightly more positive about change over time. Contributions. The results of this study indicate that there are parallels between the emotional responses of school librarians and teachers during times of change, which has implications for research on librarians in schools across the globe. The study shows that librarians with some influence have more positive experiences with change, which the researchers believe has implications for professional practice.